Strategi Peningkatan Kinerja Sektor Pariwisata Indonesia Pada ASEAN Economic Community - Victoria Lelu Sabon; Mochamad Tommy Putra Perdana; Permata Citra Stella Koropit; Wajong Christian David Pierre (Esensi: Jurnal Bisnis dan Manajemen, 2018)
Tourism industry has the important role in attracting manpower. In Indonesia, the tourism sector is one of the 11 jobs that absorb the most labor. By 2015 the tourism industry contributes 10% from Indonesia GDP total with the highest nominal in ASEAN. On the beginning of 2016 officially started the ASEAN Economic Community (AEC), that is a cooperation to improve the economic, political, and cultural performance of 10 ASEAN countries. It is necessary to improve the performance of Indonesia tourism to compete in AEC. Those are the background of doing this research. The method of this research is using qualitative research methodology with techniques of data collection by literature study and interviews, which were conducted with two interviewees from the Indonesia Ministry of Tourism. The output result of this research is recommendations for improving the performance of Indonesian tourism sector.DOI: 10.15408/ess.v8i2.5928